Sibu Goes To School - Birdsey, Bianca; Storbeck, Claudine (Roots Resources, 2018)
Sibu goes to School' follows on from 'Isipho - The Gift'. The story allows the reader to experience much of Sibu's big day as he sets off hand in hand with his beloved Gogo. They meet a new friend, Mbali, who is also different from many of the other children in their village. Mbali and Sibu, through the events of the day, discover that their special gifts can greatly help each other.
E Book - epub format
Keywords: deaf; studies; teaching; roots